Gut microbes in cardiovascular diseases and their potential therapeutic applications - Jin, Ling; Shi, Xiaoming; Yang, Jing; Zhao, Yangyu; Xue, Lixiang; Xu, Li; Cai, Jun (Protein & cell, 2021)
Microbial ecosystem comprises a complex community in which bacteria interact with each other. The potential roles of the intestinal microbiome play in human health have gained considerable attention. The imbalance of gut microbial community has been looked to multiple chronic diseases. Cardiovascular diseases (CVDs) are leading causes of morbidity worldwide and are influenced by genetic and environmental factors. Recent advances have provided scientific evidence that CVD may also be attributed to gut microbiome. In this review, we highlight the complex interplay between microbes, their metabolites, and the potential influence on the generation and development of CVDs. The therapeutic potential of using intestinal microbiomes to treat CVD is also discussed. It is quite possible that gut microbes may be used for clinical treatments of CVD in the near future.